Slovak Republic : Selected Background Issues. (IMF Staff Country Reports; Country Report ;, 1995)
This Selected Background Issues paper examines the gap between Slovak and Czech unemployment rates. The paper investigates the reasons why the Slovak unemployment rate has been considerably higher than the Czech unemployment rate. The paper highlights that the predominant cause is that employment in Slovakia declined more sharply than in the Czech Republic, particularly in 1991. The paper also analyzes the fiscal outlook for the Slovak Republic in 1995 and in the medium term. Monetary policy issues in 1994-95 are also examined.